REVITALISASI POSYANDU REMAJA MELALUI PELATIHAN DIVERSIFIKASI PANGAN LOKAL KACANG HIJAU (Vigna Radiata) MENJADI CAKE MOCAF TOPPING CRUMBLE SEBAGAI UPAYA PENCEGAHAN ANEMIA PADA REMAJA - S, Irmawati; Sanas, Nurhidayah Tiasya; SR, Nurqalbi; Sumarni, Sumarni (Fakultas Ilmu Kesehatan Universitas Borneo Tarakan, 2025)
Adolescent girls are one of the groups that are vulnerable to malnutrition. Menstruation is one of the factors that causes malnutrition, Nutritional status in adolescents is a reflection of the incidence of malnutrition in early childhood. The anemia status of adolescents in Gowa Regency was obtained from 214 adolescent girls, there were 61 adolescent girls who were anemic, of which 41 had mild anemia and 20 had severe anemia. The purpose of this service is to find out how to utilize green beans that can be processed into delicious and nutritious snacks. The methods used are counseling and training on diversification of green beans (Vigna Radiata) and demonstrations on examination and identification of anemia in adolescents. The implementation of this activity includes planning, implementation and evaluation of activities. Participants in this activity were the community in the Pabundukang Posyandu work area, Gowa Regency with a total of 20 cadres. Initial observations showed that out of 15 adolescent girls who experienced anemia from a total of 22 adolescent girls in the Pabundukang Posyandu work area. Pretest showed low knowledge of around (70%) and posttest average became high (70%), and pretest skills category unskilled (100%) and posttest average has been skilled around 29 people (96.6%). While the pretest before the intervention an average of 8 (81.5%) adolescents anemia while, after being given mocaf cake topping crumble green beans on average adolescents (92.3%) are not anemia